Legal Considerations from Judges in Supreme Court Decree No. 85 K/Pid.Sus/2013 Concerning the Acquittal of Exhibitionism Perpetrators and Their Implications as a Jurisprudence - Sultan Alwan; Jamal Hi Arsad; Rusdin Alauddin; Faisal Faisal; Fatma Laha; Amirudin Umasangaji (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Purpose of the study: This paper aims to provide a juridical analysis and the implications of the Supreme Court Decision Number 85 K/Pid.Sus/2013, where an exhibitionist perpetrator was declared to have a mental illness and he could not be held responsible. Methodology: This research used a normative juridical method with a library research approach. It was a descriptive study, which aimed to provide insight into the implication of judges in Supreme Court Decree No. 85 K/Pid.Sus/2013 for the case exhibitionism as a jurisprudence. Results: Based on the results of the Supreme Court Decision, the judge was wrong in placing exhibitionism as an excuse for eliminating criminal liability. This was based on theories and opinions which say that exhibitionism is not included in the provisions as a reason for eliminating criminal liability because exhibitionism is a type of disorder that is different from the disorders contained in the provisions regarding reasons for criminal elimination, i.e., Article 44 of the Criminal Code concerning the ability to be responsible. Exhibitionism is a sexual disorder, as opposed to a type of psychiatric disorder or psychosis contained in Article 44 of the Criminal Code. The judge also failed to base his decision on an examination by a psychiatrist who has the expertise to accurately determine the perpetrator’s mental condition. Applications of this study: This paper can be applied to prevent future occurrences of similar cases, where exhibitionists are not held accountable for their actions. This may bring more harm than good because exhibitionists will feel they have the freedom to disturb public peace by carrying out exhibitionism. Novelty/Originality of this study: No previous researchers have studied this decision and its implications. Keywords: legal consideration; supreme court; exhibitionism; implications; jurisprudence. ABSTRAK Tujuan: Artikel ini bertujuan untuk memberikan analisis yuridis dan implikasi dari Putusan Mahkamah Agung Nomor 85 K/Pid.Sus/2013, dimana seorang pelaku eksibisionis dinyatakan sakit jiwa dan tidak dapat dimintai pertanggungjawaban. Metodologi: Penelitian ini menggunakan metode yuridis normatif dengan pendekatan penelitian kepustakaan. Penelitian ini bersifat deskriptif, yang bertujuan untuk memberikan pemahaman tentang implikasi hakim dalam Keputusan Mahkamah Agung No. 85 K/Pid.Sus/2013 terhadap kasus eksibisionisme sebagai yurisprudensi. Hasil: Berdasarkan hasil Putusan MA, hakim salah menempatkan eksibisionisme sebagai dalih penghapusan pertanggungjawaban pidana. Hal ini didasarkan pada teori dan pendapat yang mengatakan bahwa eksibisionisme tidak termasuk dalam ketentuan sebagai alasan penghapusan pertanggungjawaban pidana karena eksibisionisme merupakan jenis gangguan yang berbeda dengan gangguan yang terdapat dalam ketentuan mengenai alasan penghapusan pidana yaitu Pasal 44 KUHP tentang kesanggupan untuk bertanggung jawab. Eksibisionisme adalah gangguan seksual, berbeda dengan jenis gangguan kejiwaan atau psikosis yang terdapat dalam Pasal 44 KUHP. Hakim juga tidak mendasarkan putusannya pada pemeriksaan psikiater yang memiliki keahlian untuk menentukan secara akurat kondisi kejiwaan pelaku. Aplikasi penelitian ini : Artikel ini dapat diterapkan untuk mencegah kejadian serupa di masa mendatang, di mana eksibisionis tidak bertanggung jawab atas tindakan mereka. Hal ini mungkin membawa lebih banyak kerugian karena eksibisionis akan merasa memiliki kebebasan untuk mengganggu ketentraman masyarakat dengan melakukan eksibisionisme Kebaruan/Orisinalitas: Tidak ada peneliti sebelumnya yang mempelajari keputusan ini dan implikasinya. Kata kunci: pertimbangan hukum; Mahkamah Agung; eksibisionisme; implikasi; yurisprudensi